Analysis of CO2 Emission and Economic Growth as Potential Determinants of Renewable Energy Demand in Nigeria: A Nonlinear Autoregressive Distributed Lags Approach - Muse, Bernard Olagboyega (International Journal of Energy Economics and Policy, 2021)
Concerned by the environmental and economic threats posed by fossil fuels as the source of energy, this study uses the case of Nigeria economy to understand the extent to which economic growth and carbon emissions matters for renewable energy demands. Exploring both the linear and nonlinear ARDL modelling framework, the main empirical findings are that the amplified responsiveness of the consequence of climate change has led to increase in the demand for renewable energy particularly when the underlying source of the emissions is attributable to activities in the transport sector. However, in addition to our findings of oil prices as viable for explaining renewable energy demand, this study further pointed out the economic growth as another potential for explaining renewable energy demand but vary for the boom and recession phases of the business cycle. Keywords: Renewable energy demand; CO2 emission; economic growth; nonlinear ARDL; Nigeria JEL Classifications: C22; F64; Q21; Q42, Q53 DOI: https://doi.org/10.32479/ijeep.11306